Exploring older people’s experience with augmented reality (ar) applications - Abd Malik, Sofianiza; Azuddin, Muna; Abdullah, Lili Marziana; Mahmud, Murni (Asian Research Publishing Network (ARPN), 2015)
Latest development of mobile technology has opened another opportunity for augmented reality to be implemented in the mobile device platform. Mobile augmented reality enhances mobile users experience by combining computer generated images in real environment. There have been limited studies which investigate the use of augmented reality among older people. This pilot study aims to explore older people’s experience in terms of attitude and potential barriers when they are interacting with augmented reality applications. Qualitative methods including interview, focus groups and observation were used to understand their experiences with augmented reality applications. Results indicated that, there were some barriers faced by older people in engaging augmented reality applications such as AR interface and interaction style, and familiarity with AR applications. Result showed that, they found AR applications could be beneficial for certain occasions or conditions like people in remote areas such as for outdoor and disabled users of mobile applications.